1995
DOI: 10.1142/s0192415x95000043
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture and Exercise in Body Weight Reduction and their Application in Rehabilitating Patients with Knee Osteoarthritis

Abstract: The efficacy of ear electroacupuncture on appetite and weight control was investigated in 3 separate studies. Part I: The Stomach, Hunger, or placebo ear points were stimulated in three different groups. Stimulating the Stomach, or Hunger, points was significantly more effective in appetite control than stimulating the placebo points. Part II: Stimulation of 3 pairs of ear points (Stomach, Hunger, and Shen Men) was performed on 61 obese subjects for 8 weeks. Only 43 subjects engaged, in addition, in an exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…29 Common auricular points used in the treatment of obesity include 'Hunger' and 'Stomach' points (for satiety and fullness) and 'Shenmen' (for sedation and analgesia) [34][35][36][37][38] ( Figure 2). The external ear (auricle) is innervated by several nerves, including vagus, glossopharyngeus, trigeminus, facialis, and branches (the second and third) of the cervical spinal nerves.…”
Section: Meridians and Acupointsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Common auricular points used in the treatment of obesity include 'Hunger' and 'Stomach' points (for satiety and fullness) and 'Shenmen' (for sedation and analgesia) [34][35][36][37][38] ( Figure 2). The external ear (auricle) is innervated by several nerves, including vagus, glossopharyngeus, trigeminus, facialis, and branches (the second and third) of the cervical spinal nerves.…”
Section: Meridians and Acupointsmentioning
confidence: 99%
“…Similarly, in an 8-week clinical trial of 14 obese women in Austria, individuals receiving diet+acu-puncture (point placement not described) lost more than twice as much weight than diet-only controls (7.774.4 vs 3.672.2 kg; Po0.005). 60 Shafshak 36 found that auricular electroacupuncture, administered five times a week for 3 weeks combined with a 1000-kcal/day diet, was associated with greater weight loss success (Po0.05) for the obese women treated at the 'hunger' (n ¼ 10) and 'stomach' (n ¼ 10) ear points, compared to those treated at a placebo (n ¼ 10) point. Specifically, among patients treated at the 'hunger' and 'stomach' points, 7 of 10 individuals lost 1-4 kg compared to 2 of 10 individuals in the placebo group.…”
Section: Controlled Trialsmentioning
confidence: 99%
“…Many researchers are concerned about applications of methods of oriental medicine studies, especially, preceding studies of acupuncture, herbal acupuncture, electro acupuncture and oriental herbal medicines et al treatments in obesity demonstrated the excellence (Park et al, 2003;Kim and Yoon, 1997;Larrey et al, 1992;Zhao et al, 2000;Shafshak, 1995). Adlay (Coxi lachryma-jobi) is an annual crop that has long been used in traditional Chinese medicine and as a nourishing food, including nutrients; protein 16.2%, lipid 4.65%, carbohydrate 79.17%, a small quantity of vitamin B1 330 mg% (The Korea nutrition society, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulating the auricular mouth acupoint reduces feelings of anger and has been used to treat oral ulcers. The stomach and endocrine auricular points diminish appetite and reduce the sensation of hunger, which causes feelings of satiety and fullness, promoting weight loss [1,[17][18][19][20][21][22][23]. The small intestine point treats dyspepsia, which may ultimately contribute to weight loss [23].…”
Section: Introductionmentioning
confidence: 99%